Beans and Phases of the Moon in Columella (R. r. 2. 10. 12) - Keyer, Denis (Hyperboreus, 2020)
To protect beans from weevils, Columella (R. r. 2. 10. 12) prescribes gathering them “in the dark of the moon before dawn (silente luna ... ante lucem)” and then, when they have dried on the threshing-ﬂoor, immediately beat them out, cool them and store them in the granary “before the moon begins its waxing (priusquam luna incrementum capiat)”. Yet, the moon begins its waxing immediately after the dark of the moon. Since drying of beans in the threshing-ﬂoor must take at least four or ﬁve days, it does not help to take incrementum as ‘a (noticeable) increase’. I suggest deleting priusquam luna incrementum capiat as a gloss on silente luna ... ante lucem (cf. sidus aestatis in R. r. 7. 3. 24 deleted by Hine 1984, 10 as a gloss on Caniculae). Palladius, who rephrased Columella’s advice in 7. 3. 2, retained the requirement antequam luna procedat, but changed silente luna to luna minuente. He must have worked with Columella’s text that had already been glossated, but saw the problem and moved the date for cropping back to the waning moon, in order to increase the time allowed for drying of beans and further operations “before the moon increases”.